Darbar Interior in Royal Mughal Miniature Paintings under Akbar (The Journal of Cultural Perspectives, 2023)
This study will explore the style of interior design of the Mughals, focusing on the Akbar period. Miniature paintings are one of the unique artistic features of Mughal art and also work as historical documents as any other historical record or data. Art piece of any area, dynasty or country depicts the events, culture, materials, techniques and other aspects including fashion, architecture, landscape, dresses of that particular area. The focus of this study is only on those painting that depicts court scenes that were painted by court artists. The Mughal miniatures were directly supervised by the Mughal emperors. Though the histories directly supervised by the emperors shows some affiliations and biasness but in this case, the depiction of events may be fascinated or paint as per desire of the emperor but the other field including interiors, minor arts, textile, dresses, furniture landscape portrays that period. The documentation of the Mughal art and architecture is very popular and well known but the details of interiors and its aspects is missing. So, this study will help in exploring the development and progress of Mughal Interiors including styles of furniture, thrones, carpets, wall treatments, doors, ceiling treatments